Forward osmosis process for supply of fertilizer solutions from seawater using a mixture of draw solutions. Issue 58 (13th December 2016) - Altaee, Ali; Millar, Graeme J.; Sharif, Adel O.; Zaragoza, Guillermo
Abstract: Novel desalination approaches are required to provide both drinking and agricultural water as there is ever increasing stress upon precious freshwater resources. It was our hypothesis that a modified Forward Osmosis (FO) process had the potential for production of irrigation water comprising of appropriate concentrations of fertilizers from a seawater feed. Four agents, KNO3, Na2 SO4, CaNO3, and MgCl2, plus 35 g/L seawater were used as the draw and feed solutions of the FO process. Net Driving Pressure in the FO process was manipulated either by increasing the concentration of draw solution (FO process) or by increasing feed pressure (Pressure Assisted FO (PAFO) process). A series of nanofiltration (NF) and reverse osmosis (RO) membranes were used for the regeneration of draw solution. The results suggested that a PAFO process was more energy efficient than simple FO, provided the energy relating to the brine flow from the NF/RO membrane for pressurizing the feed solution of PAFO process was used. Furthermore, this study suggested using a mixture of a primary draw solution, MgCl2, and a secondary draw solution, KNO3, for NO3 supply into the irrigation water was preferable. As such, MgCl2 provided the driving force for fresh water extraction while KNO3 was the source of fertilizer in the irrigation water. Results showed that water quality provided by application of a MgCl2  + KNO3 draw solution was better than that from KNO3 or Ca(NO3 )2 . The concentrations of NO3 and SO4 in irrigation water were within recommended levels when the diluted draw solution was regenerated by a dual stage low-pressure RO process.